Պողոս Թորոսյան Տյուրիկեցին և Աստվածաշնչի Հոբի գրքի Ա և Բ գլուխների մեկնությունը - Սարիբեկյան, Էլյա (Մատենադարան)
Poghos Tiwrikets‘i was from Tivrik, a town in the Sebastia province of historical Armenia. His ancestors had settled in Constantinople in the 16th–17th centuries. He did a great deal of scholarly and pedagogical work in Constantinople. He authored poems which are still unpublished and kept in Matenadaran. A manuscript written by Poghos contains a commentary on the first two chapters of the book of Job. He considers the Book of Job as a kind of key for explaining the events which take place in the New Testament and he draws parallels with other books of the Old Testament. The commentary touches on the person of Job and issues related to soteriology, numerology, Christology, angelology, and eschatology. He also refers to the church sacraments, especially penance. Поэт, ученый и комментатор Погос Тюрикеци был родом из города Тиврик в провинции Себастия исторической Армении. В 16-17 вв. его предки обосновались в Константинополе, где он впоследствие занимался научной и педагогической деятельностью. Погос является автором нескольких неизданных сочинений, рукописи которых хранятся в Матенадаране им. Маштоца. Одна из них – автограф, содержащий толкование двух первых глав книги Иова. Автор рассамтривает Книгу Иова как своего рода ключ к объяснению новозаветных событий. В толковании Тюрикеци проводит параллели не только с Новым Заветом, но и с другими книгами Ветхого Завета. Погос затрагивает вопросы, касающиеся личности Иова, сотериологии, нумерологии, христологии, ангелологии, эсхатологии, а также церковных таинств – в особенности покаяния.
Keywords: Աստուածաշունչ; Մեկնաբանություն